2020
DOI: 10.1016/j.jsbmb.2019.105499
|View full text |Cite
|
Sign up to set email alerts
|

Intracrinology-revisited and prostate cancer

Abstract: The formation of steroid hormones in peripheral target tissues is referred to as their intracrine formation. This process occurs in hormone dependent malignancies such as prostate and breast cancer in which the disease can be either castrate resistant or occur post-menopausally, respectively. In these instances, the major precursor steroid of androgens and estrogens is dehydroepiandrosterone (DHEA) and DHES-SO 4 . This article reviews the major pathways by which adrenal steroids are converted to the potent mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 100 publications
0
5
0
1
Order By: Relevance
“…In addition, based on the fact that high dose of kisspeptin leads to desensitization of HPG axis, kisspeptin may be applied in the treatment of sex hormone-dependent malignancies. For example, prostate cancer is a kind of androgen dependent malignancy and the current primary treatment is androgen deprivation therapy (ADT) ( 174 ). Two animal studies have confirmed that chronic administration of the kisspeptin analog, TAK-448 caused stronger inhibiting effect of HPG axis than GnRH analog and obviously suppressed testosterone and LH release, indicating its great anti-tumor growth potential ( 175 , 176 ).…”
Section: Potential Roles Of Kisspeptin In Clinical Applicationmentioning
confidence: 99%
“…In addition, based on the fact that high dose of kisspeptin leads to desensitization of HPG axis, kisspeptin may be applied in the treatment of sex hormone-dependent malignancies. For example, prostate cancer is a kind of androgen dependent malignancy and the current primary treatment is androgen deprivation therapy (ADT) ( 174 ). Two animal studies have confirmed that chronic administration of the kisspeptin analog, TAK-448 caused stronger inhibiting effect of HPG axis than GnRH analog and obviously suppressed testosterone and LH release, indicating its great anti-tumor growth potential ( 175 , 176 ).…”
Section: Potential Roles Of Kisspeptin In Clinical Applicationmentioning
confidence: 99%
“…Concerning castration-resistant PCa (CRPC), of particular importance are products of intraprostatic metabolites of adrenal androgens, the synthesis of which is independent of the gonadal–hypothalamic pituitary axis. As many as five biosynthetic pathways may take place by which adrenal steroids are converted to the potent male sex hormones, testosterone, and dihydrotestosterone [ 21 , 70 , 71 ]. Moreover, already mentioned 11-oxygenated androgens, intraprostatic metabolites of 11β-hydroxyandrostenedione, should be taken into consideration.…”
Section: Clinical Information Value Of Intraprostatic Steroid Concmentioning
confidence: 99%
“…DHT, T, and also their adrenal androgen precursors are the first at stake. Alternative pathways of androgen biosynthesis from adrenal precursors, including the backdoor pathway and important intermediate products, should be taken into account as well [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PC) that recurs after standard androgen deprivation therapy (ADT) with a GnRH agonist or antagonist (castration-resistant prostate cancer, CRPC) is in most cases still dependent on androgen receptor (AR) activity driven by residual androgens (Montgomery et al, 2008; Penning and Detlefsen, 2020; Stanbrough et al, 2006). AR activity in CRPC tumors can be further suppressed by agents such as abiraterone, which decreases adrenal androgen synthesis, or use of more effective AR antagonists, such as enzalutamide (ENZ), apalutamide, and darolutamide (Beer et al, 2014; Ryan et al, 2013; Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%